The perceptual categorization of multidimensional stimuli is hierarchically organized - Chi Chen; Livia de Hoz (iScience, 2023)
Summary: As we interact with our surroundings, we encounter the same or similar objects from different perspectives and are compelled to generalize. For example, despite their variety we recognize dog barks as a distinct sound class. While we have some understanding of generalization along a single stimulus dimension (frequency, color), natural stimuli are identifiable by a combination of dimensions. Measuring their interaction is essential to understand perception. Using a 2-dimension discrimination task for mice and frequency or amplitude modulated sounds, we tested untrained generalization across pairs of auditory dimensions in an automatized behavioral paradigm. We uncovered a perceptual hierarchy over the tested dimensions that was dominated by the sound’s spectral composition. Stimuli are thus not perceived as a whole, but as a combination of their features, each of which weights differently on the identification of the stimulus according to an established hierarchy, possibly paralleling their differential shaping of neuronal tuning.